Corona virus disease 2019 pandemic: Necessity for active engagement of the private sector - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Wolters Kluwer Medknow Publications, 2020)
The ongoing Corona Virus Disease-2019 (COVID-19) pandemic has gone beyond the capacity and capability of the public health sector and will essentially require significant support from various sectors for eventually coming out victorious against this novel viral infection. Here arises the role of private health sector, which needs to work in collaboration with the national Governments to bridge the existing lacunae and help the community and the nation at large. As the disease has already affected directly or indirectly millions of human lives across the world, the involvement of the private sector can significantly enhance the range of innovations, production and delivery of the required essentials in these times of public health emergency. In conclusion, the private sector has a crucial role to enhance the resilience of the health system and the time has come when they should work hand-in-hand with the government authorities to maximize the availability of the desired logistics and come out with innovative ways to fight the global battle against COVID-19 pandemic.